KEMEGAHAN MASJID RAYA AL-MASHUN SEBAGAI PENINGGALAN KEJAYAAN KESULTANAN DELI DI KOTA MEDAN - Ika Purnamasari; Anissa Faten Siagian; Filza Nazura; Ita Daniati Pasaribu; Josua Palentino Tampubolon; Vellyn Gracia Aurell Nainggolan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the grandeur of Masjid Raya Al-Mashun as a historitical legacy reflecting the glory of the Deli Sultanate In Medan. The research focuses on understanding the architectural uniqueness, historical value, and cultural significance of the mosque within the context of local heritage. The methodology used in this study is a qualitative apporoach through direct field research, including observation and interviews with one of the mosque administrators to obtain accurate and in-depth information. The findings reveal that Masjid Raya Al-Mashun is not only a place of worship but olso a symbol of the political power, artistic achievement, and religious influence of the Deli Sultanate. Its distinctive architectural style, which combines Middle Eastern, Indian, and European elements, demonstrates the cultural acculturation that occured during the sultanate period. Additionally, the mosque continiues to play an important role in the Medan community. Therefore, Masjid Raya Al-Mashun stands as an important historitical heritage that reflects the past glory of the Deli Sultanate and contributes to the cultural identity of the region.